Stimulasi Otak, Dimensia, Lansia PENGARUH KEGIATAN STIMULASI OTAK TERHADAP UPAYA MEMINIMALISIR DEMENSIA PADA LANSIA - w ibowo (Jurnal Keperawatan Malang, 2017)
Abstract The aging process is a lifelong process, which means decline both biologically and psychologically. The brain as a complex organ, the central regulatory system of the body and the cognitive center, is one of the organs of the body susceptible to the aging process or degenratif. Cumulative changes that often occur in the elderly is dementia. Brain stimulation activities in the elderly performed routinely can be useful to slow the occurrence of decline in brain function or dementia. The purpose of this study to know the effect of brain stimulation activities on efforts to minimize dementia in the elderly. The research design used in this research is Pre-Experiment Design with The One Group Pretest Posttest approach. The sample in this study were 30 elderly from 42 population that fulfilled inclusion criteria. This study uses non parametric statistical test, Wilcoxon test using SPSS 20 for Windows application with significance value ? ? 0.05 where the results obtained from this statistical test is p value 0,000 ? ? 0.05 which means H0 rejected and H1 accepted. The results showed that the value of ?> 0.05 means there is no difference in the level of dementia in the elderly before and after brain stimulation for 3 weeks. Keywords: Brain Stimulation, Dementia, Elderly